MANAGEMENT OF GERIATRIC NURSING CARE WITH EXCELLENT SERVICE FOR Mrs. R WITH TYPE II DIABETES MELITUS AT THE ELDERLLY SERVICE UNIT BINJAI, NORTH SUMATERA PROVINCE, IN 2025 - Muhammad Hafiz; Rosmega; Dyanti SR Butarbutar; Linda Mardiyanti Waruwu; Joyvan Saruksuk; Dodi Pana Losa Limbong; Ema Sofra Sasmita, (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
The increasing number of elderly people who experience chronic diseases, especially type II diabetes mellitus, is a challenge in gerontic nursing services. This scientific paper aims to apply gerontic nursing care management based on service excellence to Mrs. R, a 71-year-old elderly who suffers from type II diabetes mellitus, at UPTD Social Services for the Elderly Binjai, North Sumatera. This writing uses a descriptive case study approach with data collection methods through observation, interviews, and physical examinations. The main focus of nursing interventions includes managing blood glucose levels, handling skin integrity disorders due to diabetic ulcers, and controlling acute pain. The results of nursing care showed an improvement in the patient's clinical condition, characterized by a decrease in blood glucose levels from 284 mg/dl to 101 mg/dl, reduced pain, and increased patient awareness of a healthy lifestyle. The service excellent approach applied positively contributed to the patient's quality of life and supported the achievement of the Sustainable Development Goals (SDGs) target point 3.4, specifically in reducing premature mortality due to non-communicable diseases. This work confirms the importance of comprehensive, humanist, and sustainable nursing care in elderly health services in the era of globalization.